Analysis of Diffraction and Spectroscopy for bamboo Clam Shell Waste (Ensis S.P) as a Natural Source of Calcium - Umamah, Chairatul; Andi, Herman Jufri; Kartikasari, Lisma Dian (Journal of Physics and Its Applications, 2025)
Shell waste is a natural source of rich biominerals, primarily high-purity calcium carbonate (CaCO₃). This study utilized bamboo shell waste from three locations on the south coast of Pamekasan as a raw material for the synthesis of CaCO₃ compounds. The aim of this research was to characterize the composition of powdered bamboo clam shells as a source of natural calcium. The shells were prepared through several stages, including washing, drying, size reduction, and oven-drying at 105°C. They were then pulverized using a ball mill and sieved through a 200-mesh sieve. The resulting shell powder was characterized using XRF, FTIR, and XRD. The XRF results showed that the dominant chemical elements from the three locations were calcium (Ca) and its oxide compound (CaO), with average percentages of 97.95% and 98.09%, respectively. The FTIR analysis indicated the presence of CaCO₃ functional groups, namely CO₃²⁻, C–O, Ca–O, and C–H, identified by absorption peaks in range 400-4000 cm⁻¹. The XRD results confirmed that bamboo clam shells powders were contained of CaCO₃ as a single phase with the crystalline structure of aragonite (orthorhombic). Based on these results, it can be concluded that bamboo clam shell powder is a viable source of natural calcium minerals.